The Extended Continental Crust West of Islas Marías (Mexico) - Núñez, Diana; Acosta-Hernández, Jorge A.; Escalona-Alcázar, Felipe de Jesús; Pilia, Simone; Núñez-Cornú, Francisco Javier; Córdoba, Diego (Frontiers in Earth Science, 2021)
The crustal structure around the Islas Marías Archipelago has been debated for a long time. An important unresolved question is where the Rivera-North American plate subduction ends and the Tamayo fracture zone begins, from SE to NW. Results from the TsuJal project have shed light on the northwesternmost part of the Jalisco block structure. It is now clear that Sierra de Cleofas and the Islas Marías Escarpment comprise the northwestern continuation of the Middle America trench. However, other questions remain. In this paper, we present the structure of the shallow and deep crust and the upper mantle of the Islas Marías western region through the integration of multichannel seismic reflection, wide-angle seismic bathymetric and seismicity data, including records of an amphibious seismic network, OBS, and portable seismic stations, purposely deployed for this project, providing an onshore-offshore transect of 310 km length. Our findings disclose new evidence of the complex structure of the Rivera plate that dips 8°-9° underneath the NW Jalisco block as revealed by two seismic profiles parallel to the Islas Marías Escarpment. Moreover, we find five sedimentary basins and active normal faults at the edges of tectonic structures of the E-W oriented West Ranges and the N-S trending Sierra de Cleofas. Furthermore, the Sierra de Cleofas is the beginning of the active subduction of the Rivera plate beneath North America. The oceanic crust thickens and submerges towards the south while is coupled with the continental crust, from 6 km at the northern ends of the seismic profiles to 15 km in the contact region and 24 km at the coast and southern ends of them. The continental Moho was not fully characterized because of the geometry of the seismic transects, but a low-velocity layer associated with Rivera Plate subduction was observed beneath the Jalisco Block. Our results constrain the complexity of the area and reveal new structural features from the oceanic to continental crust and will be pivotal to assess geohazards in this area.